La columna informativa: un desafío de exigencia entre la omnipresente opinión. - Cantavella, Juan (Estudios sobre el Mensaje Periodístico, 2000)
The journalist’s column shows a remarkable evolution at the present time. However, a column offering new information, that the journalist himself has obtained, is not eagerly cultivated by professionals. The difficulty of obtaining unusual news in an outstanding way discourages many of them; most of them prefer to interpret what happens or, more openly, give their opinion about current events from a personal point of view.